Modulation of negatively charged particle flux from penning discharge with metal hydride cathode - Sereda, I.; Hrechko, Ya.; Azarenkov, M. (Problems of Atomic Science and Technology, 2023)
The features of modulation of negatively charged particle flux extracted along the magnetic field from Penning discharge with metal hydride cathode have been investigated. The separation of negative ions from coextracted electrons was performed by an electromagnetic filter with efficiency not worse than 90%. It is shown that electrons in the extracted flow are deeply modulated with the frequency of the diocotron instability of the anode layer, while negative ions are not. An increase in the interelectrode distance and anode length resulted in a more pronounced expression of this effect due to the minimization of the influence of the magnetic field of the filter on the discharge. Досліджено особливості модуляції потоку негативно заряджених частинок, витягнутих уздовж магнітного поля з розряду Пенінга з металогідридним катодом. Відділення негативних іонів від спільно витягнутих електронів проводилося електромагнітним фільтром з ефективністю не гірше, ніж 90%. Показано, що електрони у вилученому потоці глибоко модулюються на частоті діокотронної нестабільності анодного шару, а негативні іони − ні. Збільшення міжелектродної відстані та довжини анода призвело до більшого вираження цього ефекту за рахунок мінімізації впливу електромагнітного фільтра на розряд.